Novel extrapancreatic effects of incretin. (31st March 2016) - Yamada, Yuichiro; Tsukiyama, Katsushi; Sato, Takehiro; Shimizu, Tatsunori; Fujita, Hiroki; Narita, Takuma
Abstract: The hormonal factors implicated as transmitters of signals from the gut to pancreatic β‐cells are referred to as incretins. Gastric inhibitory polypeptide (GIP) and glucagon‐like peptide‐1 (GLP‐1) are incretins. In addition to the insulinotropic effects, we have shown, using the GIP receptor and GLP‐1 receptor‐deficient mice, that GIP and GLP‐1 have direct actions on adipocytes and the kidney, respectively. Because GIP receptors and GLP‐1 receptors are differentially expressed in a tissue‐specific manner, GIP and GLP‐1 have specific physiological activities, and further comprehensive characterization of the extrapancreatic actions of GIP and GLP‐1 is anticipated, as dipeptidyl peptidase IV inhibitors activate both GIP and GLP‐1 signaling. Abstract : GIP has been designated as gastric inhibitory polypeptide or glucose‐dependent insulinotropic polypeptide. In this minireview, we propose that GIP is gut‐derived satiation responsive polypeptide.